Porównanie relacji pamiętnikarskich z zesłania na Syberię Fiodora Dostojewskiego i Szymona Tokarzewskiego - Wilkołaska-Karpierz, Magdalena (Wydawnictwo Naukowe UAM, 2009)
The study contains a comparison of diarist's relations from exile to Syberia of Fyodor Dostoyevsky and Szymon Tokarzewski. The subject of analysis are diaries of the Polish exile, mainly Siedem lat katorgi (Seven years of penal servitude) and Fyodor Dostoyevsky's famous The House of the Dead. The author compared an image of Siberia and its inhabitants contained in both relations, a descrption of the ordeal itself and the relations between Dostoyevsky and Tokarzewski, submitted to detailed analysis, at the time when both of them were in exile. The subject of this work is also the artistic shape of both works. The article reminds of the relatively little known works of Szymon Tokarzewski to which a comparable space was devoted as to that of Dostoyevsky.
Comparison of diaristic relations from exile to Siberia of Fyodor Dostoyevsky and Szymon Tokarzewski